THE ROLE OF GLOBALIZATION IN THE CULTURAL TRANSFORMATION OF JAVANESE COMMUNITIES IN TUNTUNGAN VILLAGE - Shofiyatuzzahra; Ika Safitri; Mutia Amanda (Academic Solution Publisher, 2024)
This journal explores the impact of globalization on cultural changes among the Javanese community in Tuntungan Village, a community situated at the border between urban and rural areas in Indonesia. Utilizing a qualitative approach with ethnographic methods, this study focuses on aspects such as language, arts, traditional rituals, lifestyle, and social values. Data were collected through participant observation, in-depth interviews, and document analysis. The findings indicate an intensive mixing of Javanese, Indonesian, and foreign terms in daily communication, signaling a shift towards national and global languages. Traditional arts such as wayang kulit and ketoprak have been modified to attract younger generations, and hybrid art forms such as campursari have emerged as a creative adaptation to global influences. Traditional rituals such as Selamatetan and Mitoni are still maintained but have been simplified and adapted to fit modern lifestyles. The community's lifestyle has changed with the adoption of modern technology such as smartphones and the internet, along with a shift in consumption patterns towards global products and fast food. In education, there has been a shift from traditional knowledge-based education to a formal education system focused on global skills. Social values have also shifted from communal orientation towards higher individualism. This study emphasizes that the Tuntungan Village community actively negotiates and adapts to the currents of globalization, creating unique hybrid cultural forms. In this context, globalization not only brings cultural homogenization but also acts as a catalyst for the creation of new, complex, and dynamic cultures. The findings of this study provide important insights into how local communities respond and adapt to the challenges of globalization while maintaining the essence of their cultural identity.